The potential neuroprotective of luteolin against acetamiprid-induced neurotoxicity in the rat cerebral cortex - Albrakati, Ashraf (Frontiers in Veterinary Science, 2024)
Acetamiprid is a class of neuroactive insecticides widely used to control insect pests. The current study aimed to investigate the potential neuroprotective effects of luteolin against acetamipridinduced neurotoxicity in the rat cerebral cortex. Four equal groups of adult male rats (10 in each): control, acetamiprid (40 mg/kg for 28 days), luteolin (50 mg/kg for 28 days), and acetamiprid+luteolin cotreatment were used. Acetamiprid was shown to alter the oxidative state by increasing oxidant levels (nitric oxide (NO) and malondialdehyde (MDA) and decreasing antioxidants (glutathione (GSH), glutathione peroxidase (GPx), glutathione reductase (GR), superoxide dismutase (SOD), and catalase-(CAT), with increased activity of nuclear factor erythroid 2-related factor 2-(Nrf2). Likewise, acetamiprid increases the inflammatory response, as evidenced by increased interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α), and nuclear factor kappa B-(NF-κB). In contrast, the treatment with luteolin brought these markers back to levels close to normal, showing that it protects neurocytes from oxidative damage and the neuroinflammation effects of acetamiprid-induced inflammation. Luteolin also demonstrated a neuroprotective role via the modulation of acetylcholinesterase (AChE) activity in the cerebral cortex tissue. Histopathology showed severe neurodegenerative changes, and apoptotic cells were seen in the acetamiprid-induced cerebral cortex layer, which was evident by increased protein expression levels of Bax and caspase-3 and decreased Bcl-2 levels. Histochemistry confirmed the neuronal degeneration, as proven by the change in neurocyte colour from brown to black when stained with a silver stain. Luteolin may have a neuroprotective effect against biochemical and histopathological changes induced by acetamiprid in the rat cerebral cortex.